STRATEGI KOMUNIKASI INTERNAL DINAS PENANGGULANGAN KEBAKARAN DAN PENYELAMATAN DKI JAKARTA DALAM TANGGAP DARURAT KEBAKARAN - Imani, Rayinda Ratri; Subandi, Zera Edenzwo; Rachmad, Teguh Hidayatul (Jurnal Spektrum Komunikasi, 2025)
The high incidence of fires in Jakarta demands the Fire and Rescue Department of DKI Jakarta to maintain effective internal communication strategies. This study aims to examine how these strategies impact the department’s emergency fire response. The research employed a qualitative approach using a case study method, with data collected through in-depth interviews with six department personnel and three fire-affected residents, field observations, and documentation. Analysis was based on Karl Weick’s Organizational Information Theory, focusing on the processes of enactment, selection, and retention. The findings reveal that internal communication strategies include rapid reporting via 112 and nearby posts, information validation via telephone, use of color codes and operational terms such as “76” and “86,” and coordination through handy talkies across teams and command levels. A tiered command structure is applied based on the first responder, followed by a unified command system at the fire scene. Communication barriers identified include differences in perception, time pressure, signal disruption in areas like high-rise buildings or basements (blind spots), and environmental constraints such as traffic congestion or narrow alleyways. Nevertheless, the structured and adaptive communication strategy effectively reduces equivocality and accelerates decision-making during emergencies. This study contributes to organizational communication literature in the context of emergency response and offers insights into the importance of internal communication in managing critical information within public service organizations.